Open Reduction of the Isolated Anterior Frontal Sinus Fracture - Bonny Murizky; Al Hafiz Al Hafiz (Jurnal Kesehatan Andalas, 2020)
AbstractThe anterior wall of the frontal sinus is extremely resilient to injury. Incidents involving high-velocity impact, such as motor vehicle accidents, gunshots and sports injuries, may result in frontal sinus fractures. Clinical symptoms are associated with location and the severity. The best way to diagnose with a combination of clinical examination and CT scan. The management is mostly based on open reduction and internal fixation. The objectives was the importance of doing right management in patients with frontal sinus fracture. Reported a case of maxillofacial multiple fractures (right frontal fracture + right maxilla fracture) in a 28-year-old man, performed open reduction and internal fixation. Frontal sinus fracture is a fracture generally occurs due to traffic accidents. Anamnese of patient complaints and symptoms, physical examination and 3D CT scan can help make the diagnosis, and surgeons should give attention to the management criteria to prevent complication.